2014
DOI: 10.1136/bmjquality.u202037.w1759
|View full text |Cite
|
Sign up to set email alerts
|

Starting early: integration of self-management support into an acute stroke service

Abstract: Self-management support following stroke is rare, despite emerging evidence for impact on patient outcomes. The promotion of a common approach to self-management support across a stroke pathway requires collaboration between professionals. To date, the feasibility of selfmanagement support in acute stroke settings has not been evaluated.The Bridges stroke self-management package (SMP) is based on self-efficacy principles. It is delivered by professionals and supported by a patient-held workbook. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…More than half of the health professionals who attended the Australian Bridges workshops worked with people who were less than six months post stroke. The Bridges SSMP has recently been adapted for use in acute stroke services in the UK, to support the early introduction of strategies to empower the stroke survivor to be as independent as possible and to encourage them to participate in decision making about their initial care (Makela et al, 2014). While most focus group participants were more than six months post stroke, the usefulness of the workbook in the early stages was also highlighted, with some participants feeling that it was 'too late' now for them to receive this information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the health professionals who attended the Australian Bridges workshops worked with people who were less than six months post stroke. The Bridges SSMP has recently been adapted for use in acute stroke services in the UK, to support the early introduction of strategies to empower the stroke survivor to be as independent as possible and to encourage them to participate in decision making about their initial care (Makela et al, 2014). While most focus group participants were more than six months post stroke, the usefulness of the workbook in the early stages was also highlighted, with some participants feeling that it was 'too late' now for them to receive this information.…”
Section: Discussionmentioning
confidence: 99%
“…Key components of the Bridges SSMP training are illustrated in Figure 1. Previous studies have demonstrated preliminary proof of concept and feasibility of this programme for people living in the community post stroke (Jones et al, 2009;Jones et al, 2013;Jones et al, 2016;McKenna et al, 2015a) and in acute stroke care settings (Makela et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, we used three further methods to explore contextual and personal issues which aided and/or hampered a self-management approach in acute trauma: (1) AHP case reflections describing accounts and experiences of integrating self-management support with a patient and families; (2) Peer review to observe clinical interactions and record against a self- management fidelity checklist used in previous research20 and (3) summary of discussions about perceived barriers and facilitators to self-management support during intervention delivery (training package).…”
Section: Measurementmentioning
confidence: 99%
“…The Bridges SMP is an evidence-based educational intervention that has been tested and developed in different rehabilitation settings since 2008 13 17–20. Earlier work focused on implementation in community stroke settings but in 2013, Bridges SMP was successfully integrated into the working practices of a multidisciplinary acute stroke ward19 and in 2015 into a multidisciplinary traumatic brain injury pathway 13 21.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, stroke patients also develop extreme levels of negative emotions [10] along with high level of functional dependency [11,12]. They have poor knowledge and understanding about the reality of stroke life [13], lack skill in selfcare to overcome the challenges caused by stroke [14], and have poor adjustment to the sense of new life [15], with high caregiving burden in acute phase of disease and until 3-6 months post stroke [16]. In addition, poorly managed stroke in acute stage lead to higher possibility of living with unresolved physical problems and uncertainty that deeply changes the client's life in long term [17].…”
Section: Introductionmentioning
confidence: 99%